Association of AFF3 Gene Polymorphism rs10865035 with Rheumatoid Arthritis: A Population-Based Case-Control Study on a Pakistani Cohort - Yasir Ali; Suleman Khan; Yangchao Chen; Nadia Farooqi; Zia-Ul Islam; Mehran Akhtar; Aamir; Aisha Aman; Aftab Ali Shah; Muhsin Jamal; Fazal Jalil (Genetics Research)
Rheumatoid arthritis (RA) is one of the complex diseases with the involvement of the genetic as well as environmental factors in its onset and severity. Different genome-wide association and candidate gene studies have shown the role of several genetic variants in multiple loci/genes with ethnical and geographical variations. This study was designed to detect the association of a single-nucleotide polymorphism (SNP) rs10865035 in the AFF3 gene with the genetic background of rheumatoid arthritis (RA) in the Pakistani cohort. A total of 703 individuals, including 409 RA patients and 294 healthy controls, were genotyped using TaqMan assay and Tri primer ARMS-PCR (amplification-refractory mutation system-polymerase chain reaction) methods. The association of rs10865035 with the RA was statistically determined using different models. Interestingly, besides the homozygous recessive model (G/G vs. A/G + A/A) (OR = 1.693(1.06–2.648); P = 0.025), all other models, which included the codominant (χ2 = 5.169; P = 0.075), homozygous dominant (A/A vs. G/G + A/G) (OR = 0.867 (0.636–1.187); P = 0.41), heterozygous (A/G vs. A/A + GG) (OR = 0.491 (0.667–1.215); P = 0.49), and additive model (OR = 0.826 (0.665–1.027); P = 0.08) showed insignificant distribution of the genotypes among the cases and controls. These findings suggest that the AFF3 gene (rs10865035) has no significant role in the onset of RA in the Pakistani population.